The biology and physical ecology of Apanteles subandinus Blanchard (Hymenoptera : Braconidae), with notes on the temperature responses of Apanteles, Scutellaris Muesebeck and their host, the potato tuber worm. - Cardona Mejía, C. (University of California, 2018)
Papa-Solanum tuberosum